Incidence of central nervous system metastases in patients with human epidermal growth factor receptor 2-positive metastatic breast cancer treated with trastuzumab: A meta-analysis (Clinics, 2021)
This study aimed to estimate the incidence of central nervous system (CNS) metastases in patients with human epidermal growth factor receptor 2 (HER2)-positive metastatic breast cancer (MBC) treated with trastuzumab.Studies were identified through a literature search of electronic databases. Random-effects meta-analyses were performed to estimate the incidence rate of CNS metastases, trastuzumab therapy duration, and time from trastuzumab therapy to CNS metastasis diagnosis. A meta-analysis of odds ratios was performed to evaluate the significance of a difference in CNS metastasis incidence between patients with and without trastuzumab treatment.Thirty studies (8121 trastuzumab-treated and 3972 control patients) were included. The follow-up duration was 18.9 months (95% confidence interval [CI]: 13.8, 24.1). The trastuzumab treatment duration was 9.0 months (95% CI: 7.0, 11.0). The median interval between the start of trastuzumab therapy and CNS metastasis diagnosis was 12.2 months (95% CI: 9.5, 14.7). The incidence of CNS metastasis after the start of trastuzumab therapy was 22% (95% CI: 16, 27). The incidence of CNS metastases was significantly higher in trastuzumab-treated than in non-trastuzumab-treated patients (odds ratio: 1.39 [95% CI: 1.06, 1.82], p=0.02). The survival time from the start of the study was 23.4 months (95% CI: 19.7, 27.1) in trastuzumab-treated patients and 18.4 months (95% CI: 12.7, 24.1) in patients treated with control regimens. The survival time after the development of CNS metastases in trastuzumab-treated patients was 19.2 months (95% CI: 15.6, 25.9).Approximately 22% of patients with HER2-positive MBC who were treated with trastuzumab developed CNS metastases. However, trastuzumab-treated patients had a longer survival than patients who were not treated with trastuzumab.